Freud's Wishful Dream Book. - Welsh, Alexander (Princeton University Press, 2001)
Although it is customary to credit Freud's self-analysis, it may be more accurate, Alexander Welsh argues, to say that psychoanalysis began when The Interpretation of Dreams was published in the last weeks of the nineteenth century. Only by going public with his theory--that dreams manifest hidden wishes--did Freud establish a position to defend and embark upon a career. That position and career have been among the most influential in this century. In August 1899, Freud wrote to Wilhelm Fliess of the dream book in terms reminiscent of Dante's Inferno. Beginning from a dark wood, this modern jou.